Comparison of Certain Risk Factors Associated with Mortality Due to Coronavirus Disease 2019 in Patients at Shohadaye Kargar Hospital in Yazd, Iran (2019-2020) - Somayeh Jahanabadi; Abolhasan Halvani; Sareh Rafatmagham; Mohammadjavad Berizi (مجله دانشگاه علوم پزشکی گرگان)
Background and Objective: The coronavirus disease 2019 (COVID-19) has shown an increasingly rapid progression in individuals with underlying diseases or comorbidities, frequently culminating in mortality. This study was conducted to compare certain risk factors associated with mortality due to COVID-19 in patients at Shohadaye Kargar Hospital in Yazd. Methods: This descriptive study was conducted on 120 surviving (recovered) polymerase chain reaction (PCR)-positive COVID-19 patients (55 males and 65 females) with a mean age of 52.8 ± 18.88 years and 60 deceased PCR-positive COVID-19 patients (34 males and 26 females) with a mean age of 75.4 ± 15.4 years at Shohadaye Kargar Hospital in Yazd, Iran during 2019-2020. Census sampling was performed on all confirmed positive cases of COVID-19. Variables including age, gender, cigarette use, presence of diabetes, hypertension, pulmonary and cardiovascular diseases, and malignancies, which were collected in Yazd Province by the Provincial Coronavirus Committee, were evaluated. Results: The variables of gender, cancer, cigarette use, asthma, and deep venous thrombosis (DVT) did not show any statistically significant differences between the recovered and deceased groups. The variables of diabetes, hypertension, ischemic heart disease, chronic obstructive pulmonary disease (COPD), and age showed statistically significant differences between the two groups (P<0.05). Conclusion: Advanced age and the presence of hypertension and diabetes are considered risk factors in COVID-19 patients.